2016
DOI: 10.1002/cjas.1378
|View full text |Cite
|
Sign up to set email alerts
|

Framing the usefulness of eHRM in talent management: A case study of talent identification in a professional services firm

Abstract: As talent management evolves from intuitive to evidencebased decision-making, the role of electronic Human Resource Management (eHRM) to gather, distribute, and analyze data becomes more critical. However, surprisingly few academic studies investigate the role of technology in talent management. Drawing on a qualitative case study of talent management in a large professional services firm, this paper critically examines how eHRM information technologies are framed as useful within talent identification discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 51 publications
0
35
0
1
Order By: Relevance
“…Collings, 2014;Collings et al, 2018;Gallardo-Gallardo & Thunnissen, 2016;Sonnenberg et al, 2014;Thunnissen et al, 2013), sensitivity to the potentially conflicting interests of the different internal actors, at different levels, is largely neglected in empirical TM research (Huang & Tansley, 2012;Iles et al, 2010). One exception here is Wiblen (2016), who showed how organizational actors drew upon different understandings when identifying talents. Two different talent identification discourses were therefore present at the studied organization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Collings, 2014;Collings et al, 2018;Gallardo-Gallardo & Thunnissen, 2016;Sonnenberg et al, 2014;Thunnissen et al, 2013), sensitivity to the potentially conflicting interests of the different internal actors, at different levels, is largely neglected in empirical TM research (Huang & Tansley, 2012;Iles et al, 2010). One exception here is Wiblen (2016), who showed how organizational actors drew upon different understandings when identifying talents. Two different talent identification discourses were therefore present at the studied organization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For the MTN group to maintain a diverse and sustainable pool of talent which will meet the strategic goals of the firm, the group has over the years committed resources towards the training and capacity building of its staff. An integrated approach, that is strategically aligned is used in MTN during the process of talent identification as suggested by Wiblen, (2016). It is reported that the group committed about R383 million for development of talent and skills for its staff.…”
Section: Hrm Practices At Mtn Ugandamentioning
confidence: 99%
“…Egorova et al () indicated three different perspectives of stakeholders—strategic, tactical, and operational—as possessing different conditions for success. In addition to the perception, the idiosyncratic style of use by different stakeholders can often diminish various value‐producing characteristics of an IS (Wiblen, ; Arjomandy, ; Bondarouk, Schilling, & Ruël, ). These aspects related to post‐implementation success can be sufficiently addressed through a proper stakeholder engagement.…”
Section: Methodsmentioning
confidence: 99%